Cytokine‐regulated Th17 plasticity in human health and diseases. Issue 1 (6th November 2020) - Cerboni, Silvia; Gehrmann, Ulf; Preite, Silvia; Mitra, Suman
Summary: Upon activation, naïve CD4 + T helper (Th) cells differentiate into distinct Th effector cell lineages depending on the local cytokine environment. However, these polarized Th cells can also adapt their function and phenotype depending on the changing cytokine environment, demonstrating functional plasticity. Here, Th17 cells, which play a critical role in host protection from extracellular pathogens and in autoimmune disorders, are of particular interest. While being able to shift phenotype within their lineage, Th17 cells can also acquire characteristics of Th1, Th2, T follicular helper (Tfh) or regulatory T cells. Th17 cell identity is determined by a spectrum of extracellular signals, including cytokines, which are critical orchestrators of cellular immune responses. Cytokine induces changes in epigenetic, transcriptional, translational and metabolomic parameters. How these signals are integrated to determine Th17 plasticity is not well defined, yet this is a crucial point of investigation as it represents a potential target to treat autoimmune and inflammatory diseases. The goal of this review was to discuss how cytokines regulate intracellular networks, focusing on the regulation of lineage‐specific transcription factors, chromatin remodelling and metabolism, to control human Th17 cell plasticity. We discuss the importance of Th17 plasticity in autoimmunity and cancer and present current strategies and challenges in targeting pathogenic Th17 cells with cytokine‐based approaches, considering human genetic variants associated with altered Th17 differentiation. Finally, we discuss how modulating Th17 plasticity rather than targeting the Th17 lineage as a whole might preserve its essential immune function while purging its adverse effects. Abstract : Orchestra of cytokines regulates phenotypic and functional plasticity of non‐pathogenic and pathogenic Th17 cells in human health and diseases.